2017
DOI: 10.1186/s12884-017-1612-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with postnatal care for newborns in Zambia: analysis of the 2013-14 Zambia demographic and health survey

Abstract: BackgroundThe importance of postnatal care cannot be overemphasised. Various studies undertaken worldwide have found that PNC is critical for the survival of newborns. However, in Zambia, despite much emphasis by the government and various international Organisations on the need for PNC, coverage continues to be low. This study attempted to assess the demographic and socio-economic factors associated with newborns' receipt of PNC and the timing of first PNC in Zambia.MethodsBased on data from the 2013-14 Zambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
51
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 20 publications
12
51
4
1
Order By: Relevance
“…The study findings suggest that missed opportunities to provide PNC may explain why the increasing coverage of institutional deliveries in Tanzania, now at 63%, has not had as much impact on maternal and newborn morbidity and mortality as hoped. As has been reported in other studies, however, this analysis found that early postnatal checks for both mother and newborn were more likely if mothers had made at least four ANC visits during pregnancy and if they gave birth by caesarean section [53,54,55]. Thus, promoting ANC services may have a positive impact on PNC.…”
Section: Discussionsupporting
confidence: 67%
“…The study findings suggest that missed opportunities to provide PNC may explain why the increasing coverage of institutional deliveries in Tanzania, now at 63%, has not had as much impact on maternal and newborn morbidity and mortality as hoped. As has been reported in other studies, however, this analysis found that early postnatal checks for both mother and newborn were more likely if mothers had made at least four ANC visits during pregnancy and if they gave birth by caesarean section [53,54,55]. Thus, promoting ANC services may have a positive impact on PNC.…”
Section: Discussionsupporting
confidence: 67%
“…Women who started their rst antenatal visit in the recommended timeframe and had at least four antenatal care visits were more likely utilize PNC than their counterparts. This nding is consistent with ndings of several studies (23)(24)(25)(26)(27)(28)(29). Because ANC is a time when mothers are educated about childbirth and childcare practices, those who follow the ANC guidelines might be better informed about PNC guidelines.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, this analysis found that the odd of having a timely PNC check-up was higher among women whose educational status was secondary/higher as compared to those with no education. This result was in line with a number of studies (23)(24)(25)29).The more the maternal educational attainment, the more likely the awareness and knowledge of bene ts to be derived to comply with more health recommendations; this is in part due to the fact that they may understand better. Additionally, women who are educated are more likely to have paid employment and to contribute to the household expenditure and consumption and that means more power in decision-making process in household issues including utilization of health services (28).…”
Section: Discussionsupporting
confidence: 87%
“…Receiving adequate post-natal care is, thus, crucial for improving the health status of both mothers and newborns [1719]. Although the World Health Organization recommends routine post-natal care provided to all mothers and newborns, in practice, this seems not to be the case [20].…”
Section: Discussionmentioning
confidence: 99%
“…Data from Zambia health and demographic survey reported that on average, the was 55% of newborns received post-natal checks. If it was disaggregated by delivery place, 58% of newborns born at healthcare facilities had health checks, and 48% of newborns delivered at home [20]. Recently, a study in Sri Lanka reported that the proportion of mothers who received post-natal health checks were 82.6% at the national level [7].…”
Section: Discussionmentioning
confidence: 99%